The Impact On The Implementation Of Presidential Regulation Number 20 Of 2018 Concerning The Use Of Immigrant Worker - Fahmi, Muhammad Irfan Nur; Nasrullah, Nasrullah (Media of Law and Sharia, 2021)
In regulating the constitutional order, it should have a clear legal basis based on the viewpoint of a democratic political system. With the issuance of Presidential Regulation Number 20 of 2018 concerning the Use of Immigrant Worker, it is hoped that it can become a government effort in overcoming problems in the availability of jobs for domestic workers, this is due to the use of immigrant workers which has an impact on domestic worker in Indonesia and deviant articles and not in accordance with what is contained in this rule. Therefore, the issuance of this Presidential Regulation discusses licensing and regulations that must be obeyed and implemented by both employers and workers themselves. It is the same as entering the new normal era which is caused by the existence of the Covid-19 and become pandemic; so that permits for the entry and exit of immigrant workers into Indonesia must be clearer and stronger, in order to minimize the movement and spread of the virus. This study used qualitative research with a normative juridical case approach, this study also was conducted to analyze how the Presidential Regulation Number 20 of 2018 gave impacts especially to the domestic worker caused by stipulated this regulation; not only that, this study also discussed the mechanism of monitoring and evaluating this presidential regulation. The results of this research showed that there was some impacts caused by the existence of the Presidential Regulation Number 20 of 2018 both from the use and licensing of immigrant workers as well as from the articles contained in this regulation.